The JNK signaling pathway in intervertebral disc degeneration - Liu, Ganggang; Gao, Lu; Wang, Yuncai; Xie, Xinsheng; Gao, Xuejiao; Wu, Xingjie (Frontiers in Cell and Developmental Biology, 2024)
Intervertebral disc degeneration (IDD) serves as the underlying pathology for various spinal degenerative conditions and is a primary contributor to low back pain (LBP). Recent studies have revealed a strong correlation between IDD and biological processes such as Programmed Cell Death (PCD), cellular senescence, inflammation, cell proliferation, extracellular matrix (ECM) degradation, and oxidative stress (OS). Of particular interest is the emerging evidence highlighting the significant involvement of the JNK signaling pathway in these fundamental biological processes of IDD. This paper explores the potential mechanisms through the JNK signaling pathway influences IDD in diverse ways. The objective of this article is to offer a fresh perspective and methodology for indepth investigation into the pathogenesis of IDD by thoroughly examining the interplay between the JNK signaling pathway and IDD. Moreover, this paper summarizes the drugs and natural compounds that alleviate the progression of IDD by regulating the JNK signaling pathway. This paper aims to identify potential therapeutic targets and strategies for IDD treatment, providing valuable insights for clinical application.